Structure and dynamics of titania – poly(N-vinyl caprolactam) composite hydrogels. Issue 1 (27th November 2019) - Timaeva, O. I.; Kuz'micheva, G. M.; Pashkin, I. I.; Czakkel, O.; Prevost, S.
Abstract : The morphologies and dynamics of poly( N -vinyl caprolactam) based hydrogels with titania nanoparticles in different states are studied. A hierarchical structure of hydrogels with both the static structure and dynamics are established. Abstract : The morphologies and dynamics of poly( N -vinyl caprolactam) (PVCL) based hydrogels with titania nanoparticles in different states (native, air-dried to a constant weight and swollen in H2 O or D2 O) are studied by a combination of complementary techniques: wide angle X-ray scattering, small angle neutron scattering, neutron spin echo spectroscopy, differential scanning calorimetry. The results suggest the presence of different structural types of water leading to different properties of the hydrogels. We propose a hierarchical structure of hydrogels spanning from the molecular to the microscopic scale consistent with both the static structure (polymer mesh size, association of the nodes of crosslinks and microchains of PVCL) and the dynamics (rate of relaxation of polymer chains, hydrodynamic polymer-polymer correlation length). The presence of nanoscale titania does not change the molecular structure and nanostructure due to its aggregation into meso-domains, but does affect the microstructure, changing the response rate to a temperature jump from 20 to 50 °C. Titania nanoparticles do not change the equilibrium swelling degree of hydrogels.